2008
DOI: 10.1183/09031936.00089808
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of heteroresistance to isoniazid and rifampin of Mycobacterium tuberculosis in Tashkent, Uzbekistan

Abstract: Heteroresistance of Mycobacterium tuberculosis (MTB) is defined as the coexistence of susceptible and resistant organisms to anti-tuberculosis (TB) drugs in the same patient. Heteroresistance of MTB is considered a preliminary stage to full resistance. To date, no mechanism causing heteroresistance of MTB has been proven.Clinical specimens and cultures from 35 TB patients from Tashkent, Uzbekistan, were analysed using the Genotype MTBDR assay (Hain Lifescience, Nehren, Germany), which is designed to detect gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 23 publications
(18 reference statements)
5
100
2
Order By: Relevance
“…This study revealed the presence of heteroresistance, which is defined as the coexistence of susceptible and resistant microorganisms to antituberculosis drugs in the same patient (27). Alternatively, other less-studied molecular mechanisms, such as gene duplications, may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed the presence of heteroresistance, which is defined as the coexistence of susceptible and resistant microorganisms to antituberculosis drugs in the same patient (27). Alternatively, other less-studied molecular mechanisms, such as gene duplications, may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mixed allelic variants could be explained by heteroresistance (the presence of FQ-susceptible and -resistant populations of bacteria as a result of ongoing resistance development) (39). Heteroresistance and mixed allelic variants in gyrA codons have been previously reported in areas with high rates of drug resistance (9,18,31). Such cases should be interpreted clinically with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical importance of heterogeneous M. tuberculosis populations is particularly relevant for patients where both drug- susceptible and drug-resistant strains are present in the same sputum (2, 36). Thus, heteroresistance poses a significant challenge to genetics-based drug resistance diagnostics, as the sensitivity of detecting genomic mutations conferring drug resistance will be dependent on the complexity of the bacterial population structure within the specimen being analyzed, including the number of different mutations conferring resistance to a single anti-TB drug as well as the ratio between resistant and susceptible clones (9,16). In most instances, primary resistance would be associated with a homogeneous population of bacilli harboring the same single mutation.…”
Section: Discussionmentioning
confidence: 99%